2015
DOI: 10.1016/j.jalz.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of white matter hyperintensities on neurodegeneration in mild cognitive impairment

Abstract: INTRODUCTION It is unclear whether white matter hyperintensities (WMH), MRI markers of small-vessel cerebrovascular disease, promote neurodegeneration and associated clinical decline in Alzheimer’s disease (AD), or simply co-occur with recognized pathogenic processes. METHODS In 169 patients with mild cognitive impairment (MCI), followed for 3 years, we examined the association of 1) baseline regional WMH and cerebral spinal fluid (CSF) derived total-tau with entorhinal cortex atrophy rates, as a marker of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 54 publications
(54 reference statements)
7
71
0
4
Order By: Relevance
“…The present study showed that WMH increased odds for dementia (and ADNP) in participants with autopsy-confirmed ADNP above and beyond the contributions of APOE ε4 carrier status. These findings extend in vivo studies that associate WMH with accelerated cognitive decline and brain atrophy, and increased risk for AD dementia [2328,31,32,68], but were without autopsy confirmation of underlying ADNP. Taken together, the present findings corroborate recent research studies that propose WMH to be a contributor to the pathogenesis of AD [30,35].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The present study showed that WMH increased odds for dementia (and ADNP) in participants with autopsy-confirmed ADNP above and beyond the contributions of APOE ε4 carrier status. These findings extend in vivo studies that associate WMH with accelerated cognitive decline and brain atrophy, and increased risk for AD dementia [2328,31,32,68], but were without autopsy confirmation of underlying ADNP. Taken together, the present findings corroborate recent research studies that propose WMH to be a contributor to the pathogenesis of AD [30,35].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies that have examined the association between WMH and CSF total tau in AD dementia also provide evidence that WMH promote tau pathology and exacerbate the effects of tau on clinical status; additionally, the relationship between WMH and CSF total tau may be independent of beta-amyloid [32,69]. WMH are typically interpreted to be MRI markers of small vessel CBVD, which may explain their association with ADNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested from this data that WMHs, by interacting with tau abnormalities, may exert direct pathological influence on the development and progression of dementia (Tosto et al, 2015). The pathology underlying WMHs is traditionally associated with cerebrovascular changes and compromised integrity of the blood brain barrier, which together result in a region of poor perfusion and thus enhanced MRI signals (Black et al, 2009; Young et al, 2008).…”
Section: Loss Of Myelination Is a Pathological Hallmark Of The Agimentioning
confidence: 78%
“…In addition, another study by Tosto et al 37 demonstrated that white matter hyperintensities promote tau accumulation and not vice versa, further proving that cerebrovascular changes precede LOAD-related neurodegenerative processes. The protective effect of hypertension on LOAD and its association with stroke, which in turn increases the risk for LOAD, depicts a complex scenario of multiple intercorrelated causal effects that cannot be reduced to a single variable-outcome association.…”
Section: Discussionmentioning
confidence: 95%